Vulnerability of existing RC building with seismic damage scenarios: case of educational buildings in Mostaganem city - Bendehiba, Sabeur (2023)
The present work aims to assess the large-scale seismic vulnerability of a set of 55 reinforced concrete educational establishments of different typologies (approximately 516 constructions) located within the urban perimeter of the city of Mostaganem. Among them, 328 buildings were constructed in accordance with the Algerian seismic regulation (built after 1980), while 188 constructions were built without a seismic design code (built before < 1980). This classification corresponds to the application/creation of this regulation following a major earthquake in Chlef (El Asnam) in 1980. Using the RISK-UE lm1 method, the vulnerability index was assessed based on a visual inspection for each building using an on-site inventory form to determine the general sources of seismic vulnerability. This strategy allows the prioritization of constructions according to their typologies, considering the structural system of the building and modifying factors, such as code level, maintenance condition, number of floors, plan and elevation irregularities, soil morphology, etc. The application of this methodology generated several seismic scenarios expressing the probable damage to the constructions, and the following results were suggested: The first two seismic scenarios have no damage corresponding to intensities I = 5; 6. The third scenario is characterized by low to negligible damage corresponding to intensity I = 7. Moderate damage was observed for the fourth seismic scenario (I = 8), while the fifth scenario generated by seismic intensity I = 9 presents moderate to heavy damage. The sixth scenario, with intensity I = 10, exhibits a relatively heavy damage balance. Starting from intensity I = 11, the damage becomes heavy to very heavy for the seventh scenario. Finally, the eighth scenario describes total destruction of the constructions. The results obtained from the application of this methodology on the educational buildings have been integrated into a Geographic Information System (GIS) environment to better understand the seismic behavior of the structures and to estimate the magnitude of seismic risk. This facilitates simulation and enables efforts to be made to take concrete preventive measures to strengthen existing educational buildings, thus reducing the negative impact of future earthquakes.